IMPLEMENTASI PEMBELAJARAN NILAI ISLAM MENGGUNAKAN PENDEKATAN HABITUS DI SEKOLAH DASAR - najib, rifqi_ihsanu; Katni, Katni; Safawi, Imam; Salsabila (LPPM STAI Muhammadiyah Probolinggo, 2025)
Implementing Islamic values ​​learning using the habitus approach in schools can be done by instilling Islamic values ​​in every aspect of students' lives. The habitus approach emphasizes the importance of habituation and direct experience in shaping students' character and behavior. This study aims to analyze the implementation of Islamic values ​​learning using the habitus approach in elementary schools, as well as its supporting and inhibiting factors. This study uses a qualitative descriptive approach, field research type, with the researcher as the key instrument conducting data collection through interviews, observations, and documentation of 10 instruments. Data analysis involves data reduction, display, and verification. The implementation of Islamic values ​​using the habitus approach in elementary school students in SERPAMA Cambodia, encompasses the values ​​of faith, worship, and morals. The values ​​of faith are implemented in students' daily lives, fostering the habit of practicing and believing in the power of Allah SWT, angels, the Holy Book, the Prophets and Messengers, the Day of Judgment, and destiny. Material is provided both in and outside the classroom, as well as in an environment that supports learning related to these Islamic values. Supporting factors in the implementation of Islamic values ​​using the habitus approach include enthusiasm for learning and having competent teachers. Teachers consistently encourage students to do good deeds, and this is done repeatedly for students. The school has adequate facilities to support learning. Meanwhile, inhibiting factors include the background, the Islamic education system that only exists in elementary schools, and students' activities that are still divided between helping parents who work far away from the area.